GAME TECHNOLOGY IN THE PERSONAL DEVELOPMENT - Oydinoy Xushvaqtova; Alimjanova Laylo Xamadullaevna (Journal of new century innovations, 2022)
The importance of game technology in the personal development of students and the importance of game technology in the development students’ creative abilities.